Effect of adhesive cementation strategies on the bonding of y-tzp to human dentin - Alves, M. L.L.; Campos, F. [UNESP]; Bergoli, C. D.; Bottino, M. A. [UNESP]; Özcan, M.; Souza, R. O.A. (Operative Dentistry, 2016)
This study evaluated the effects of different adhesive strategies on the adhesion of zirconia to dentin using conventional and self-adhesive cements and their corresponding adhesive resins. The occlusal parts of human molars (N=80) were sectioned, exposing the dentin. The teeth and zirconia cylinders (N=80) (diameter= 3.4 mm; height=4 mm) were randomly divided into eight groups according to the factors surface conditioning and cement type (n=10 per group). One conventional cement (CC: RelyX ARC, 3M ESPE) and one self-adhesive cement (SA: RelyX U200, 3M ESPE) and their corresponding adhesive resin (for CC, Adper Single Bond Plus; for SA, Scotchbond Universal Adhesive-SU) were applied on dentin. Zirconia specimens were conditioned either using chairside (CJ: CoJet, 30 lm, 2.5 bar, four seconds), laboratory silica coating (RC: Rocatec, 110 lm, 2.5 bar, four seconds), or universal primer (Single Bond Universal-UP). Nonconditioned groups for both cements acted as the control (C). Specimens were stored in water (378C, 30 days) and subjected to shear bond strength (SBS) testing (1 mm/min). Data (MPa) were analyzed using two-way analysis of variance and a Tukey test (a=0.05). While surface conditioning significantly affected the SBS values (p=0.0001) (C,RC=CJ=UP), cement type did not (p=0.148) (CC=SA). The interaction terms were significant (p=0.014). Failure types were predominantly adhesive. Air-abrasion and the use of the universal primer improved the bond strength of zirconia to dentin compared to the control group, regardless of the type of resin cement used.